Peran Cyber Counseling dalam Mengatasi Problematika Siswa di Masa Pandemi (Studi Kasus di SMPN 1 Sumenep) - Fitri Ari Novi Jayanti; Nazlah Hidayati (Tafhim Al-'Ilmi, 2022)
Abstract Guidance and counseling as a means for students to get help in overcoming problems that cannot be resolved are some of the important elements for education so that teaching and learning activities run well. E-counseling or online counseling is the best solution in overcoming problems experienced by students during a pandemic like this time. The purpose of this research is to know the various kinds of problems faced by students during the pandemic, to know the role and strategies of cyber counseling in overcoming these problems, and to determine the supporting and inhibiting factors in the application of cyber counseling at SMP Negeri 1 Sumenep. This research was conducted at SMP Negeri 1 Sumenep, Madura. The type used is qualitative research with a non-participant case study approach. Data collection using in-depth interview method through online media. The results of this study indicate that the role of cyber counseling during this pandemic is very much needed to help students reduce the burden and overcome the problems they face, especially those that disturb them so that they do not focus on the learning process. Key Words: Cyber counseling, Counseling during the Pandemic, Student Problems during the Pandemic.